A survey of the problems of the high school students of the University of the Philippines - Fernandez, Ligaya 1908- ([Quezon City University of the Philippines], 1954)
This is an investigation of the different problems of high school students at the University of the Philippines based on the Mooney Problem Checklist. This includes the specific problems that are prevalent among the male and female students, the problems that worry them the most, students' opinion regarding talking to someone about their problems and when they would like to talk regarding their problems.
Bibliography: l. 141-144.
Thesis (M.Ed.)--University of the Philippines, 1954
Typewritten
Vita
Keywords: University of the Philippines -- High School -- Students